Very Low Temperature Magnetoresistance in the Quadrupole Ordered System PrV2Al20. (January 2016) - Shimura, Y; Tsujimoto, M; Zeng, B; Zhang, Q; Balicas, L; Sakai, A; Nakatsuji, S
Abstract: We measured magnetoresistance of the quadrupole ordered system PrV2 Al20 with a Γ3 doublet ground state under high-DC magnetic field up to 30 T. The field dependence of the magnetoresistance is strongly different between H ∥ [111] and H ∥ [110] in spite of the cubic crystal structure. For H ∥ [110], we observed a jump with distinct hysteresis between 13 and 16 T and a shoulder structure in the field of 8 T at 23 mK.